PELAKSANAAN PENEGAKAN HUKUM TERHADAP PELAKU TINDAK PIDANA PERKOSAAN DITINGKAT PENYIDIKAN - Ecky Widi Prawira; Fatkhurohman Fatkhurohman; Sirajuddin Sirajuddin (Pascasarjana Ilmu Hukum, Universitas Widyagama Malang, 2022)
The legal process against the perpetrators of the crime of rape at the investigation level is the first step in providing protection for victims who have experienced trauma. The legal process against the perpetrators of the crime of rape at the investigation level can be carried out with Restorative justice without overriding the customary law that applies in certain communities. The form of prevention efforts carried out by the police are preventive and repressive (action efforts) such as providing counseling and conducting socialization in Tamiyang Layang Regency in order to increase awareness of all possible occurrences of rape crimes against women and children in the family and community environment, as well as conducting patrols. at night where children and teenagers are dating so that immoral acts can be minimized.